MAQĀṢID DIRĀSAT AL-MA'RIFAH AL-TĀRĪKHIYYAH FĪ AL-QUR'ĀN AL-KARĪM - Kourime, Souad (Universitas Islam Negeri Ar-Raniry, 2024)
The Holy Quran is the undisputed first source of science in the Islamic heritage. However, this source has faded in some human sciences that have been affected by positivist thought and Western epistemology, including the science of history. This paper aims to restore consideration of the Holy Quran as a methodological and cognitive source for historical studies. In order to achieve this goal, this paper invoked two aims of the study of historical knowledge in the Holy Qur’an, namely the purpose of methodological necessity and the purpose of cognitive sufficiency of the Qur’an as a source in the study of history. This paper relied on the qualitative approach, which starts by induction and description, then qualitative analysis, and ends with drawing conclusions. As a result, the paper invested the purposes of studying Qur’anic knowledge in the field of history to prove the cognitive value and methodological accuracy of the historical knowledge enshrined in the Holy Qur'an.